Reframing governance: competition fatalism and autonomy in central-local relations - Entwistle, Tom et al (2016)
Much of the work on contemporary governance points either to a strong central government that continues to operate hierarchically or else to a relatively weak centre which relies on network forms of coordination. In place of the choice between hierarchy and networks, the cultural theory pioneered by Mary Douglas draws our attention to five distinctive social environments characterized in terms of hierarchy, individualism, egalitarianism, fatalism and autonomy. Based on an analysis of survey data collected from 488 local government managers across England, Scotland and Wales, this article uses the Douglas framework to understand patterns of governance. While the data lend support to the strong centre theorists in revealing little evidence of a central-local partnership and continuing reliance on regulatory-type instruments, we find this more a recipe for competition and fatalism than hierarchy. Our data also point to significant differences in governance style both across services and between countries. - Reproduced.
Keywords: Central government; Public administration